2016
DOI: 10.2217/bmm-2016-0283
|View full text |Cite
|
Sign up to set email alerts
|

Association Between IL-27 Gene Polymorphisms and Risk of Papillary Thyroid Carcinoma

Abstract: These findings showed that IL-27 rs153109 and rs17855750 might be related to the tumorigenesis of PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Several studies examined the association between DOI:10.31557/APJCP.2020.21.9.2507 IL-27 polymorphisms and the risk of various cancer (Wei et al, 2009;Zhao et al, 2009;Guo et al, 2012;Huang et al, 2012;Pan et al, 2012;Tao et al, 2012;Peng et al, 2013;Munretnam et al, 2014;Tang et al, 2014;Zhang et al, 2014a;Zhang et al, 2014b;Lyu et al, 2015;Pu et al, 2015;Zhang et al, 2015;Zhou et al, 2015;Ge and Xiao, 2016;Wang et al, 2016;Yu et al, 2016;Nie et al, 2017;Ghavami et al, 2018). The findings were controversial, though it is difficult to clarify the inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies examined the association between DOI:10.31557/APJCP.2020.21.9.2507 IL-27 polymorphisms and the risk of various cancer (Wei et al, 2009;Zhao et al, 2009;Guo et al, 2012;Huang et al, 2012;Pan et al, 2012;Tao et al, 2012;Peng et al, 2013;Munretnam et al, 2014;Tang et al, 2014;Zhang et al, 2014a;Zhang et al, 2014b;Lyu et al, 2015;Pu et al, 2015;Zhang et al, 2015;Zhou et al, 2015;Ge and Xiao, 2016;Wang et al, 2016;Yu et al, 2016;Nie et al, 2017;Ghavami et al, 2018). The findings were controversial, though it is difficult to clarify the inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that IL-27 possesses antitumor activities against a variety of tumor types (Nagai et al, 2010;Di Carlo et al, 2014;Yoshida and Hunter, 2015;Yoshimoto et al, 2015). IL-27 is a polymorphic gene and several studies examined the association between IL-27 gene polymorphisms and risk of various cancers including, non-small-cell lung cancer (NSCLC) (Ge and Xiao, 2016), acute lymphoblastic leukemia (ALL) (Ghavami et al, 2018), nasopharyngeal carcinoma (NPC) (Wei et al, 2009;Pan et al, 2012), colorectal cancer (CRC) (Guo et al, 2012;Huang et al, 2012;Lyu et al, 2015), prostate cancer (PCa) (Munretnam et al, 2014), papillary thyroid carcinoma (PTC) (Zhang et al, 2015;Nie et al, 2017), hepatocellular carcinoma (HCC) (Peng et al, 2013), renal cell carcinoma (RCC) (Pu et al, 2015), osteosarcoma (Tang et al, 2014), esophageal cancer (Tao et al, 2012), cervical cancer (Wang et al, 2016), endometrial cancer (Yu et al, 2016), ovarian cancer (Zhang et al, 2014b), breast cancer (Zhang et al, 2014a), glioma (Zhao et al, 2009), and bladder cancer (Zhou et al, 2015). However, the findings of these studies have been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no studies on the relationship between autoimmune polyglandular syndromes and IL27 polymorphisms, and more studies are needed to explore the relationship between them in the future. Existing studies reported that rs153109 AG and AG/GG genotypes, rs17855750 GT and GT/GG genotypes of IL27 gene significantly increased the risk of PTC, both rs153109 and rs17855750 of IL27 gene contributed to the increased risk of PTC (22). Moreover, there is another study which showed that rs153109 of IL27 gene may be associated with the decreased risk for lymph node metastasis of PTC (39).…”
Section: Discussionmentioning
confidence: 99%
“…AITD patients were recruited from Department of Endocrinology, Jinshan Hospital of Fudan University. The inclusion criteria of all patients have been described previously (12, 22). Both GD and HT were diagnosed according to the international diagnostic criteria (14).…”
Section: Methodsmentioning
confidence: 99%
“…TC led the fifth most common cancer in women in the United States [2], while the estimates of cancer incident cases and deaths were 143.9 thousand and 6500 respectively in China [3]. Although the exact pathophysiologic mechanisms of TC remained elusive, accumulating evidence indicated that the inter-individual genetic factors, especially the single nucleotide polymorphisms (SNPs) in tumor-associated genes took essential part in the genetic susceptibility to TC [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%